From Oxymoron to Intersection: An Epidemiology of Legal Research - D. Manderson; Richard Mohr (Law Text Culture, 2002)
The foregoing articles about research in and around law reflect a broad conception of what it is to be a legal scholar. The views and experiences of the authors gathered here are probably no more radical or heterodox than those to be found in any of the earlier editions of this journal or the many others devoted to themes of law, society, culture and contemporary legal theory. Having brought these people together to reflect on what it is that they think and do when researching in law, we have raised 'the legal research question'.1 In these closing remarks we would like to reflect on the practical implications of the epistemologies which emerge from the views of these authors.